Survei Tingkat Skill Related Fitness Pada Siswa-Siswi Sekolah Dasar Negeri Gugus 1-4 Fase C di Kecamatan Kedungkandang Kota Malang - Munawiri, Mohamad Falih; Wiguno, Lokananta Teguh Hari (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
Carrying out this study aims to determine the value of physical fitness related to skills in students at SDN Gugus 1-4, Kedungkandang District, Malang City, because there is no data related to physical fitness and sports teachers have never measured students' physical fitness levels. This research method uses quantitative descriptive methods with survey techniques. The subjects taken in this research were 95 students using the Proportionate Stratified Random Sampling technique. The Indonesian Student Fitness Test (TKSI) is the instrument used in this research. Descriptive statistics in this study were used to analyze the data. The results of the study concluded that 53.47% of students from Gugus 1-4 State Elementary School, Kedungkandang District, Malang City were dominant in the poor category, with details of 6.74% or 8 students in the good category, 31.58% or 50 students in the medium category, 14.70% or 35 students in the poor category. , 0% or 2 students are classified as very poor.